2011
DOI: 10.1016/j.cellimm.2011.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of NLRP3 and AIM2 inflammasome gene expression levels in gingival fibroblasts by oral biofilms

Abstract: Periodontal disease is an inflammatory condition that destroys the tooth-supporting tissues. The inflammation is initiated by oral bacteria in the form of multi-species biofilms, and is dominated by cytokines of the IL-1 family. IL-1 activation and processing is regulated by Caspase-1, within intracellular protein complexes, known as "inflammasomes". The present study employed culture supernatants of in vitro supragingival and subgingival biofilms, to challenge human GF cultures for 6h. The gene expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
81
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 43 publications
8
81
1
Order By: Relevance
“…The relative effect of A. actinomycetemcomitans leukotoxin and Cdt on IL-1β and IL-18 expressions by the cells was also considered in this study. Of note, IL-18 was expressed at lower levels that IL-1β, also in line with recent findings in macrophages [59] and gingival fibroblasts [58]. Although none of the A. actinomycetemcomitans knock-out mutant strains differentially regulated IL-1β expression compared to the wild-type strain, they all appeared to enhance IL-18 expression levels by the cells, but this did not prove to be statistically significant, due to the large standard deviation between experiments.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The relative effect of A. actinomycetemcomitans leukotoxin and Cdt on IL-1β and IL-18 expressions by the cells was also considered in this study. Of note, IL-18 was expressed at lower levels that IL-1β, also in line with recent findings in macrophages [59] and gingival fibroblasts [58]. Although none of the A. actinomycetemcomitans knock-out mutant strains differentially regulated IL-1β expression compared to the wild-type strain, they all appeared to enhance IL-18 expression levels by the cells, but this did not prove to be statistically significant, due to the large standard deviation between experiments.…”
Section: Discussionsupporting
confidence: 83%
“…Although it is difficult to assess the net functional effect of the differential regulation of NLRP3 and ASC, bacterial pathogens may strategically perturb the expression of various inflammasome components, in order to manipulate the innate immune responses [57]. To this extent, supragingival and subgingival biofilms were shown to differentially regulate the expression of the NLRP3 and AIM2 inflammasomes in gingival fibroblasts, denoting the different pathogenic potential of these two biofilm variants for periodontal diseases [58]. actinomycetemcomitans does not affect the intracellular levels of pro-Caspase-1 [20], although its leukotoxin can promote Caspase-1 activation [17] and enhanced IL-1β production.…”
Section: Discussionmentioning
confidence: 99%
“…Others studies have shown that supragingival and subgingival biofilms differently regulate the gene expressions of NLRP3 and AIM2 inflammasomes in human gingival fibroblasts (Bostanci et al, 2011), and the downregulation of NLRP3 and IL-1β expression is partly induced by P. gingivalis present in subgingival biofilms (Belibasakis et al, 2013). Although NOD1 and NOD2 are involved in the recognition of periodontal pathogens and in the immune responses modulation (Okugawa, 2010), the effect of its activation in osteoclast is still unknown.…”
mentioning
confidence: 99%
“…The best-defined inflammasomes are nucleotide-binding oligomerization domain-like receptors (NLRs), which are intracellular pattern recognition receptors. NLRs recognize pathogen-or danger-associated molecular patterns and induce the activation of cysteine proteinase caspase 1 (CASP1), which then activates IL-1β maturation (7). Among inflammasomes, the NLR family, pyrin domain containing 3 (NLRP3) is thought to play a role in periodontal disease (8).…”
Section: Introductionmentioning
confidence: 99%
“…Among inflammasomes, the NLR family, pyrin domain containing 3 (NLRP3) is thought to play a role in periodontal disease (8). The NLRP3 inflammasome consists of an NLRP3 scaffold, CASP1, and adaptor molecule called the apoptotic speck protein containing a C-terminal caspase recruitment domain (ASC), which mediates the interaction of NLRP3 and CASP1 (7). NLRP3 exerts its inflammatory effects through ASC (9), and co-expression of NLRP3, with activation of CASP1 by ASC resulting in IL-1β activation (10).…”
Section: Introductionmentioning
confidence: 99%